Handbook of sustainable development through green engineering and technology - Bali, Vikram (Boca Raton : CRC Press, 2022)
"Green Engineering involves the designing, innovation, and commercialization of products and processes which promote sustainability without eliminating both efficiency and economic viability. This handbook focuses on Sustainable Development through Green Engineering and Technology and is intended to address the applications and issues involved in their practical implementation. New range of renewable energy technologies modified for providing green engineering will be described in this handbook. It will explore all green communication technologies, including but not limited to, green smart buildings, fuel-efficient transportation, paperless offices, and energy efficiency measures, for providing green engineering for the future. The handbook acts as a comprehensive reference book for the identification of the development of programs and sustainable initiatives within the current legislative framework and aims to be of great interest to researchers, faculty members, and students across the globe"--
OCLC-licensed vendor bibliographic record.
Keywords: Sustainable engineering; TECHNOLOGY / Manufacturing